2015
DOI: 10.3390/f6041239
|View full text |Cite
|
Sign up to set email alerts
|

Biomass, Carbon and Nutrient Storage in a 30-Year-Old Chinese Cork Oak (Quercus Variabilis) Forest on the South Slope of the Qinling Mountains, China

Abstract: Chinese cork oak (Quercus variabilis) forests are protected on a large-scale under the Natural Forest Protection (NFP) program in China to improve the ecological environment. However, information about carbon (C) storage to increase C sequestration and sustainable management is lacking. Biomass, C, nitrogen (N) and phosphorus (P) storage of trees, shrubs, herb, litter and soil (0-100 cm) were determined from destructive tree sampling and plot level investigation in approximately 30-year old Chinese cork oak fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
2
11
0
2
Order By: Relevance
“…Biomass of all age classes in this study were all larger than that of natural Quercus wutaishanica forest (young and middle-aged stands 76.02 Mg·ha −1 , near-mature stands 79.35 Mg·ha −1 , mature stands 96.71 Mg·ha −1 ) in Ziwuling of Loess Plateau [43]. Consistent with previous studies, the biomass of stems accounted for the largest proportion, roots secondly, leaves the least in tree tissues of all age classes [25,42]. The biomass of understory vegetation was 1.99-5.66 Mg·ha −1 in different age classes, and the biomass of understory vegetation and litter accounted for small proportion of the stand biomass (young stands 11.47%, middle-aged stands 5.77%, near-mature stands 6.57%, mature stands 8.06%), which was also consistent with previous studies [25].…”
Section: Biomass Allocation Of Quercus Variabilis Natural Secondary Fsupporting
confidence: 79%
See 3 more Smart Citations
“…Biomass of all age classes in this study were all larger than that of natural Quercus wutaishanica forest (young and middle-aged stands 76.02 Mg·ha −1 , near-mature stands 79.35 Mg·ha −1 , mature stands 96.71 Mg·ha −1 ) in Ziwuling of Loess Plateau [43]. Consistent with previous studies, the biomass of stems accounted for the largest proportion, roots secondly, leaves the least in tree tissues of all age classes [25,42]. The biomass of understory vegetation was 1.99-5.66 Mg·ha −1 in different age classes, and the biomass of understory vegetation and litter accounted for small proportion of the stand biomass (young stands 11.47%, middle-aged stands 5.77%, near-mature stands 6.57%, mature stands 8.06%), which was also consistent with previous studies [25].…”
Section: Biomass Allocation Of Quercus Variabilis Natural Secondary Fsupporting
confidence: 79%
“…Consistent with previous studies, the biomass of stems accounted for the largest proportion, roots secondly, leaves the least in tree tissues of all age classes [25,42]. The biomass of understory vegetation was 1.99-5.66 Mg·ha −1 in different age classes, and the biomass of understory vegetation and litter accounted for small proportion of the stand biomass (young stands 11.47%, middle-aged stands 5.77%, near-mature stands 6.57%, mature stands 8.06%), which was also consistent with previous studies [25]. This may be associated with forest management, canopy structure, and soil conditions, which affect the growth of understory vegetation by light, nutrition and hydrothermal conditions [26].…”
Section: Biomass Allocation Of Quercus Variabilis Natural Secondary Fsupporting
confidence: 78%
See 2 more Smart Citations
“…However, an increasing number of studies have indicated that C content varied significantly among plant organs (Alriksson and Eriksson, 1998;Bert and Danjon, 2006;Yao et al, 2015), life forms (Tolunay, 2009;Fang et al, 2010;Cao and Chen, 2015), biomes (He et al, 2006;Martin and Thomas, 2011;Martin et al, 2015), and even across individuals (Elias and Potvin, 2003;Uri et al, 2012;Martin et al, 2013). Using the default value of 50 % as biomass C con-version factor which ignores the variation of C content may lead to biases (Zhang et al, 2009;Martin and Thomas, 2011;Rodrigues et al, 2015).…”
Section: Introductionmentioning
confidence: 99%